Desenvolvimento e caracterização fisico-química de um selante resinoso com propriedades antimicrobianas associadas à incorporação do extrato do caule de Schinopsis brasiliensis (Braúna) - Lima, Rodolfo Xavier de Sousa (2023)
Introduction: dental sealants have a preventive and therapeutic activity in the prevention and treatment of dental caries. However, there are no reports of these materials with antimicrobial properties and the addition of phytotherapy molecules would be an option to solve this limitation. Objectives: to evaluate the antimicrobial properties of the Fluroshield™ sealant with the addition of the stem extract of Schinopsis brasiliensis (Braúna), as well as the potential for releasing the active ingredient, degree of conversion and immediate enamel bond strength. Methodology: this is an experimental in vitro study. Braúna barks were dried at 40 ± 1 °C and the ethanolic extract was obtained by percolation of Schinopsis brasiliensis bark powder. The commercial sealant Fluroshield™ was enriched with the proportions by mass (g) [0% (Control), 20%, 10%, 5%, 2.5% and 1.25%]. The evaluation of the Inhibition of Biofilm Formation was carried out, the release of the active principle was measured with Ultra High Performance Liquid Chromatography (UHPLC), the immediate bond strength (BS) to the dental tissue was evaluated with microshear and the degree of conversion (DC) with Micro-Raman. Final values were submitted to Shapiro-Wilky (p > 0.05) and Levene normality tests. Parametric data were submitted to analysis of variance (one-way ANOVA) with Tukey's post-test (p <0.05) and nonparametric data through the Kruskal-Wallis test with Dunn's post-test using the GraphPad Prism software 8 and Microsoft Excel 2018. Results: materials with a higher % of extract had a lower DC, there was no statistically significant difference for BS between the different groups, there was release of the active principle in all materials and groups with 20% and 10 % of extract by mass were able to inhibit biofilm formation similarly to the positive control (0.12% chlorhexidine). Conclusion: the addition of Schinopsis brasiliensis extract in concentrations between 10% and 20% is a promising alternative for obtaining antimicrobial properties in resin sealants.